Microbiota-derived short chain fatty acids in pediatric health and diseases: from gut development to neuroprotection - Hsu, Chou-Yi; Khachatryan, Lusine G.; Younis, Nada Khairi; Mustafa, Mohammed Ahmed; Ahmad, Nabeel; Athab, Zainab H.; Polyanskaya, Angelina V.; Kasanave, Elena Victorovna; Mirzaei, Rasoul; Karampoor, Sajad (Frontiers in Microbiology, 2024)
The infant gut microbiota undergoes significant changes during early life, which are essential for immune system maturation, nutrient absorption, and metabolic programming. Among the various microbial metabolites, short-chain fatty acids (SCFAs), primarily acetate, propionate, and butyrate, produced through the fermentation of dietary fibers by gut bacteria, have emerged as critical modulators of host-microbiota interactions. SCFAs serve as energy sources for colonic cells and play pivotal roles in regulating immune responses, maintaining gut barrier integrity, and influencing systemic metabolic pathways. Recent research highlights the potential neuroprotective effects of SCFAs in pediatric populations. Disruptions in gut microbiota composition and SCFA production are increasingly associated with a range of pediatric health issues, including obesity, allergic disorders, inflammatory bowel disease (IBD), and neurodevelopmental disorders. This review synthesizes current knowledge on the role of microbiota-derived SCFAs in pediatric health, emphasizing their contributions from gut development to neuroprotection. It also underscores the need for further research to unravel the precise mechanisms by which SCFAs influence pediatric health and to develop targeted interventions that leverage SCFAs for therapeutic benefits.